Seed biology and possibility of improvement of seed germination capacity on Virginia mallow (Sida hermaphrodita L. Rusby) - Kurucz, Erika; Fári, Miklós (Acta Agraria Debreceniensis, 2014)
Sida hermephrodita or Virginia mallow is a perspective perennial herb in the Malvaceae family able to yield a biomass crop through the last two decades. Additionally, the plants have a lot of uses and benefits for instance it can use as a fodder crop, honey crop, ornamental plant in public gardens. It has favourable features like fast growing and resistance against the disease and climatic fluctuations, etc. Sida is in the beginning phase of domestication therefore it has a serious disadvantage: the low and slow germination as a big part of wild plants. Due to the expressly low germination percent the need of seed showing of driller is should tenfold, 200 thousand seeds/acre instead of 10–20 thousand what is not available and expensive Therefore practical purposes of our research of seed physiology was to increase the seed germination percent in a available, basically wild Sida population. In the first stage of our experiments we examined two factors relating to seed germination percent and seed germination power during our research: the influence of hot water treatment and the effect of exogenous or endogenous infection of seed. However, in our germination tests, utilizing scarified seeds with hot water (65 oC, 80 oC, 90 oC), from 29,3% to 46% germinated from those samples which were collected from the population of Sida hermaphrodita in Debrecen. The average germination for all season was 5–10% without treatment and rinsed using hot water up to almost 50%. When physically scarified used, the oldest seeds showed the best germination (46%) after the hot water operation in spite of the previous studies. We discovered that apparently there are close relationship between the seed fresh weight or water uptake capability and the percentage of infection. Following these recognition we modified our technique,in such a way that we fractionated the seeds based on their fresh weight/or relative density before we carried out the treatment. When we filtered the floating seeds on the surface of water, the hot water treatment was performed considerably better on the sunk seeds after separation. Therefore, by this special priming process we were able to reach 80% germination capacity of Virgina mallow seeds under laboratory conditions (26 oC without illumination).